Female Genital Mutilation: A Religio-cultural Sensitive Issue Determining Maternal Healthcare Choices among Somali Women in Dadaab Refugee Camp, Kenya - Gitome, Josephine; Kahumbi, Newton; Mainah, Muthoni; Kituku, Jacqueline M.; Mwoma, Teresa; Ndegwa, Priscilla; Bagelman, Jennifer (European Scientific Journal, ESJ, 2023)
This paper focuses on Kenya’s development challenges in maternal health care, especially the impact of traditional birth attendants (TBAs) and female genital mutilation (FGM) among the refugees. The study identifies four objectives: to discuss the persistence of FGM among Somali women in Ifo Refugee Camp; to establish the hospital process of providing maternal health care to mothers who have gone through FGM; to find out the level of preparedness of the midwives to handle mothers with religio-cultural concerns such as prayer and non-involvement of male nurses; and how the practice of FGM contributes to the preference of TBA by mothers. This study assumes that midwives’ training may not have effectively addressed FGM, a social-cultural sensitive issue affecting childbirth and care. The specific support of midwives in refugee camps contexts also remains limited. A qualitative research approach was used in the study, involving Snowballing sampling method, in-depth interviews, and focus group discussions (FGDs). These methods brought out pertinent issues that make TBAs the preferential option for some mothers despite the presence of level 4 category hospitals in the refugee camps. In case of birth complications, the mother’s choice for TBA delays the family’s decision to take her to the hospital and for healthcare workers to save mother and child. The shortage of midwives and the presence of male midwives in hospitals make some Somali mothers seek assistance from TBAs. There is a need to contextualize midwifery training by enhancing the curriculum with evidence-based/mother-centered skills.